Pengembangan Sistem Informasi Taman Pendidikan Al Qur’an Menggunakan Framework Java Spring - Yance Sonatha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Al Qur'an Education School (TPA) is a non-formal Islamic educational institution that aims to teach the Qur'an from an early age. One of them is Al HIjrah TPA which is located in Nanggalo District, Padang, Indonesia. So far, the academic process in TPA still collects data manually. This study used the System Development Life Cycle (SDLC) method and aimed to produce an information system that can manage data and present information about the TPA. Users can access it anywhere and anytime. PIECES framework is used to analyze system requirements, while the Unified Modeling Language (UML) method is used in the design stage. In developing the system, the Java programming language is used with Framework Spring. The resulting system has 3 types of access rights namely system administrators, teachers and students. The system can later be accessed online.